2009
DOI: 10.1111/j.1537-2995.2009.02276.x
|View full text |Cite
|
Sign up to set email alerts
|

A new strategy to improve the cost‐effectiveness of human immunodeficiency virus, hepatitis B virus, hepatitis C virus, and syphilis testing of blood donations in sub‐Saharan Africa: a pilot study in Burkina Faso

Abstract: In resource-limited settings, the implementation of a sequential strategy appears as a pragmatic solution to promote safe blood supply and ensure sustainability of the system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 19 publications
2
14
2
Order By: Relevance
“…In the blood bank of Tete, only the cost of the rapid HCV screening tests represents an additional amount of at least 7,000 USD annually, for a few prevented infections. Although innovative testing strategies could be explored in Tete [27], it is likely that HCV screening could become really cost-effective only if the prices of available rapid tests were drastically reduced.…”
Section: Discussionmentioning
confidence: 99%
“…In the blood bank of Tete, only the cost of the rapid HCV screening tests represents an additional amount of at least 7,000 USD annually, for a few prevented infections. Although innovative testing strategies could be explored in Tete [27], it is likely that HCV screening could become really cost-effective only if the prices of available rapid tests were drastically reduced.…”
Section: Discussionmentioning
confidence: 99%
“…Prevalence was higher among first-time and female donors 68. A study to estimate the prevalence of transfusion-transmissible HIV infection in 2 groups of blood donors at Douala city over the period 1995 to 2004 indicated that the prevalence of HIV ranged from 2.2% to 8.12% at the Douala University and 7.89% at the blood bank of Laquintinie Hospital 69. Remunerated and family replacement donors are at more risk of being HIV positive 70.…”
Section: Challenge Of Transfusion-transmissible Infectionsmentioning
confidence: 99%
“…A cross-sectional study undertaken to determine the seroprevalence of HBsAg among 1410 apparently healthy prospective blood donors in Nigeria observed an overall seroprevalence of 18.6% 73. A study to estimate the prevalence of transfusion-transmissible HBV in 2 groups of blood donors at Douala city over the period 1995 to 2004 indicated that the seroprevalence for HBV ranged from 6.10% to 16% for donors at Douala University, while at the blood bank of Laquintinie Hospital the prevalence was 6.91% 69. Between January and August 1999, a total of 7277 blood donors at various health centers in Kinshasa, Democratic Republic of the Congo were screened for HBsAg using the ELISA technique.…”
Section: Challenge Of Transfusion-transmissible Infectionsmentioning
confidence: 99%
“…In Burkina Faso, few published data are available on the prevalence of syphilis in the population. Previous studies have reported a regional variation in the prevalence of syphilis among pregnant women [4, 5] and blood donors[6, 7]; however, most of these studies had several limitations. In fact, they involved a small sample size and the sociodemographic factors associated with the risk of syphilis infection were not systematically studied.…”
Section: Introductionmentioning
confidence: 99%